Post-Ugi Acid-Catalyzed Fragmentation and Trapping: An Unprecedented Approach towards Novel Bis(indolyl)acetamides - Bhoraniya, Rinkal B.; Desai, Shiv R.; Koladiya, Mahesh; Bhopekar, Vidhi V.; Patel, Swati H.; Modha, Sachin G. (Synlett, 2024)
An unprecedented post-Ugi Brønsted acid catalyzed fragmentation followed by in situ trapping of the alkylideneindolenine intermediate by indole nucleophiles was developed to furnish novel bis(indolyl)acetamides. The amide fragment formed during this acid-catalyzed fragmentation of the Ugi adduct was also isolated and characterized. The carboxylic acid and amine components of the Ugi reaction were carefully chosen to permit a simple water wash for the removal of the amide fragment to obtain the desired bis(indolyl)acetamides in a pure form.
Keywords: Ugi reaction; indoles; multicomponent reaction; bisindolylacetamides; fragmentation